Reconstruction of northeast Asia spring temperature 1784–1990 - M. Ohyama; H. Yonenobu; J.-N. Choi; W.-K. Park; M. Hanzawa; M. Suzuki (Climate of the Past, 2013)
We describe a first attempt of wide-area dendroclimatic reconstruction, based upon seven spring temperature-sensitive chronologies from the ring widths of living trees, in Japan and Korea. Mean March–May temperature derived from a gridded land air temperature dataset (CRUTEM4) between 35–40° N and 125–140° E was reconstructed for the period of AD 1784–1990. Of the seven, two Japanese chronologies were eliminated during the calibration trials. The reconstruction accounted for 19.4% of the temperature variance in the calibration period, and is considered to be skillful for estimating interannual-to-interdecadal variations and not for long-term change. This reconstruction showed remarkably similar fluctuations to regional dendroclimatic reconstructions in Japan and Korea, indicating the past spatial coherency of spring temperatures in the region. The reconstruction was validated against other climate proxies. A fairly good agreement was found with cold periods as estimated from documentary records in southeast China and Japan. The west Japan temperature series recovered from instrumental records also showed a reasonable agreement with the reconstruction. On the other hand, the reconstruction did not show clear abrupt depressions after the Laki and the Tambora eruptions. These comparisons revealed that dendroclimatic spatial reconstruction in this area offers a good potential for reconstructing long-term and large-scale past temperature patterns for northeast Asia.